Penerapan Terapi Bermain Mewarnai Gambar untuk Menurunkan Kecemasan pada Anak Usia Pra Sekolah Akibat Hospitalisasi: RSUD Dr. Tjitrowardojo Purwerejo - Priati Priati; Despita Pramesti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hospitalized children often experience anxiety due to the unfamiliar hospital environment, frightening medical procedures, and separation from family. This anxiety, if left untreated, can negatively impact a child's psychological well-being and hinder the healing process. One non-pharmacological intervention that can be implemented to help reduce anxiety in children is play therapy. This therapy is a fun and developmentally appropriate approach, one of which is through coloring activities. This study aims to describe the application of coloring play therapy in reducing anxiety levels in preschool-aged children undergoing hospitalization. The research design used a case study with two preschool-aged children treated in the Dahlia Ward of Dr. Tjitrowardojo Regional General Hospital, Purworejo. The anxiety measurement instrument used the FIS (Face Image Scale), which allows the assessment of children's facial expressions as an indicator of anxiety levels. The results showed that before therapy, subject I was in the mild anxiety category with an FIS score of 2, while subject II was in the moderate anxiety category with an FIS score of 4. After coloring play therapy, both children experienced a significant decrease in anxiety levels, namely becoming no longer anxious (FIS score 1). These findings indicate that play therapy, including coloring activities, is effective in reducing anxiety in hospitalized preschool children. This intervention could be an easy, affordable, and enjoyable alternative for healthcare providers in providing holistic care to children.